Changes in Self-Reported Health and Psychosocial Outcomes in Older Adults Enrolled in Sedentary Behavior Intervention Study. Issue 7 (September 2019) - Matson, Theresa E.; Anderson, Melissa L.; Renz, Anne D.; Greenwood-Hickman, Mikael Anne; McClure, Jennifer B.; Rosenberg, Dori E.
Purpose: To estimate changes in self-reported health and psychosocial factors associated with a 12-week sedentary behavior intervention for older adults. Design: Exploratory secondary analysis of pilot randomized controlled trial. Setting: Kaiser Permanente Washington Subjects: Sixty adults aged 60 to 89 with body mass index ≥30 kg/m 2 . Intervention: Participants were randomized to the I-STAND intervention or control group. I-STAND involved 6 coaching sessions, a study workbook, Jawbone UP activity tracker to prompt breaks from sitting, and activPAL feedback on objective sitting time. Measures: At baseline and 12-week follow-up, participants completed a survey with validated measures of self-reported health outcomes (depression, stress, memory/concentration, sleep, pain, ability to do daily activities, energy, and quality of life) and modified scales measuring psychosocial factors (perceived benefits/barriers, social support, self-efficacy, and sedentary habit strength) regarding sedentary behavior. Analysis: Generalized linear models assessed associations between group assignment and change in each self-reported health and psychosocial score, adjusting for baseline scores. Results: I-STAND participants demonstrated improvements in self-efficacy (β = 0.35, 95% confidence interval [CI]: 0.10 to 0.60) and reduced habit strength (β= −0.23, 95% CI: −0.42 to −0.04) compared to control participants. There were no significant differences in self-reported health outcomes, although power was limited in this exploratory analysis. Conclusion: A sedentary behavior reduction intervention for older adults resulted in improvements for some psychosocial factors. Health outcomes may require longer than 12 weeks to observe improvements.